Peculiarities of Thermally Activated Migration of Subvalent Impurities in Cu-Doped Y-Stabilized ZrO2 Nanopowders Produced From Zr Oxychlorides - Korsunska, Nadiia; Polishchuk, Yulia; Baran, Mykola; Nosenko, Valentyna; Vorona, Igor; Lavoryk, Serhyi; Ponomaryov, Semyon; Marie, Olivier; Portier, Xavier; Khomenkova, Larysa (Frontiers in Materials, 2018)
The influence of chlorine on spatial distribution of subvalent dopants and oxygen vacancies’ content in Cu-doped Y-stabilized ZrO2 nanopowders was studied as a function of calcination temperature (500-1000°C) and Cu content (1 and 8 mol %). The powders were prepared by co-precipitation technique from a mixture of zirconium oxychloride, yttrium and copper nitrates. The powders were studied by X-ray diffraction, Auger spectroscopy, attenuated total and diffuse reflectance, as well as by electron paramagnetic resonance methods. The increase of calcination temperature stimulates structure transformation, variation of oxygen vacancies content in the grains and amount of dispersed CuO at their surface. All these changes depend on Cu content being controlled by surface-volume copper redistribution: in-diffusion of copper (below 800°C) and its out-diffusion (at 800-1000°C). The transformation of surface entities (Cu2Cl(OH)3 and Cu-OH complexes) followed by the formation of CuO was observed. At low Cu content (1 mol%), the amount of oxygen vacancies and CuO varies significantly and non-monotonically with Tc rise, while for higher Cu content (8 mol%), they change slightly. Chlorine was found to be present in the grain bulk with the content nearly equal to Cu content. It acts as compensator for Cu charge that prevents the appearance of oxygen vacancies. The Cu-Cl interaction hampers Cu out-diffusion from the grains, phase transformation and formation of CuO at their surface. The latter reduces the catalytic activity of the powders in the CO PROX reaction. Among all the powders, the highest CO conversion (about 80%) was found to be demonstrated by the powders calcined at 600°C contained 1 mol% of CuO.